Compulsory Schooling and Inclusion in Secondary Education: tensions and translations (Itinerarios Educativos, 2019)
The present work constitutes an advance ofa research work entitled: «Inclusion and compulsoryschooling in secondary education: analysis of nationaleducational policies and their translations in the provinceof Santa Fe, Argentina». This research is carriedout at the Faculty of Educational Sciences and Psychopedagogyof Universidad Abierta Interamericana,in the city of Rosario, Santa Fe. The general objectiveof this work is to identify and analyze the notions ofinclusion in national education policies for secondaryeducation and their translations in the province of SantaFe from 2006 till present.This first advance addresses an analysis of the relationships,dialogues, tensions, and translations about com-pulsory schooling and inclusion in secondary educationas discussed in the guidelines provided by UNESCOand national regulations such as the Argentine EducationAct, resolutions number 84/2009 and 93/2009 ofthe Federal Council of Education of Argentina, and theComplete Secondary Program developed in the provinceof Santa Fe. The underlying meanings are analyzedin relation to inclusion and compulsory schooling insecondary education and the ways in which these categoriesare captured and implemented in the policieswith the aim of elucidating certain continuities andruptures in their senses.
Keywords: secondary education · compulsory schooling · inclusion · educational policies · translations